Fugitive Aesthetics: Embodiment, Sexuality and Escape from Alcatraz. Issue 1 (March 2015) - Chare, Nicholas
Abstract : This essay builds on Jacques Rancière's exploration of the relationship between aesthetics and politics to analyse queer sexuality in Don Siegel's prison film Escape from Alcatraz . The film both illustrates and embodies what Rancière refers to as a redistribution of the sensible, an opening up of a new way of making sense of the world. In Escape from Alcatraz this sense-making is bound up with same-sex desire. Rancière is usually concerned with aesthetic practices linked to class struggle. This essay, however, examines how Rancière's ideas are also illuminating in relation to subjugated sexual experiences.